ANALYSIS OF MARKETING COSTS, PROFIT MARGINS AMONG ACTORS, MARKETING CHANNEL EFFICIENCY, AND FARMER'S SHARE DISTRIBUTION IN THE PALM OIL MARKETING SYSTEM: A LITERATURE REVIEW BASED ON A VALUE-ADDED APPROACH - Farida Akbarina; Tehedi Tehedi (INJOSEDU: International Journal of Social and Education, 2026)
This study analyses marketing costs, profit margins between actors, marketing channel efficiency, and farmer's share distribution in the Indonesian palm oil marketing system through a literature review. The results show high marketing costs of Rp450-1,200/kg (22-30% of the fresh fruit bunch price), margin disparities (farmers 25-35% vs mill 35-42% added value), average channel efficiency of 24.6% (ideal <15%), and a national farmer's share of 71.4% (standard >80%) due to long supply chains and local oligopsony. The value-added approach reveals a redistribution potential of 12-18% through channel shortening, e-FFB trading digitalisation, and plasma partnerships recommended to increase systemic efficiency by 15-20% and the welfare of farmers managing 40% of the national area